Food emulsions, fourth edition - Friberg, Stig E. (Marcel Dekker, 2011)
Upholding the standards that made previous editions so popular, this reference focuses on current strategies to analyze the functionality and performance of food emulsions and explores recent developments in emulsion science that have advanced food research and development. Written by leading specialists in the field, the Fourth Edition probes the latest technologies in food emulsion assessment for excellence in food product design and focuses on methods of emulsion characterization and investigation. It contains new discussions on droplet analysis, surface forces, and the rheology of emulsions and examines essential components of everyday foods such as breads, condiments, margarine, and cheese.